(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Agriculture is the main source of raw materials for the growth of the gross domestic product and ensuring food security. The article describes the need to obtain food products by processing agricultural products. Some problems in the field of food processing are indicated. Also, the volume of food products produced in the Namangan region in the last year was analyzed, relevant conclusions were given.